Rethinking Multi-Channel Protocols in Wireless Sensor Networks - Liang, Chieh-Jan Mike; Terzis, Andreas (HotEmNets (ACM Workshop on Hot Topics in Embedded Networked Sensors), 2010)
The availability of multiple frequency channels on modern radios has provided a way to improve networking performance. Nevertheless, current multi-channel protocols lack the architectural consistency and flexibility to support a diverse set of applications. In this paper we argue that it is necessary to integrate channel switching to the emerging wireless sensor network architecture and propose a way to decompose the problem into two reusable components: the channel allocation component that is integrated with network layer protocols and a shared channel synchronization component at the MAC layer. Furthermore, we outline how existing multi-channel protocols can be re-factored to comply with the proposed architecture and present ViR, an initial implementation of the channel synchronization component. Finally, using realistic applications synthesized from existing protocols, we show how ViR reduces conflicts among protocols and reduces packet losses.